Perlindungan Jiwa, Harta, dan Kehormatan dalam Hadis Hadis dan Relevansi dengan Hak Asasi Manusia Kontemporer - Sri Nilawati Saragih; Hery Ardiyanto; Ahmad Hujaifah Tanjung; Farid Adnir (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study discusses the protection of life, property, and dignity in the hadiths of prophet muhammad (peace be upon him) and its relevance to contemporary human rights (hr). The aim of this research is to explain how hadith provides a normative foundation for safeguarding human dignity from various forms of harm, injustice, and violation. The method used is library research with a qualitative-descriptive approach by analyzing relevant hadith literature and modern human rights sources. The findings show that hadith strongly emphasizes the protection of life (ḥifẓ al-nafs), property (ḥifẓ al-māl), and honor (ḥifẓ al-‘irdh) as part of the objectives of islamic law (maqāṣid al-sharī‘ah). These principles are closely aligned with modern human rights concepts, particularly the protection of the right to life, property rights, and human dignity. Therefore, it can be concluded that hadith teachings are not only important in a religious context but also highly relevant in supporting universal human rights in the contemporary era.